Comparativo das características das carnes de frango caipira e industrial da região oeste do Rio Grande do Norte - Silva, Débora Cristina Fernandes da (Universidade Federal Rural do Semi-Árido, 2017)
The aim of this study was to make a comparison of physicochemical, microbiological and sensory properties of meat of free-range and industrial chicken strains from local trade. Analyses of chemical composition, color, pH, shear force and sensory analysis were made. The chromaticity revealed higher intensity of yellow for free-range broiler chicken meat (b = 11.56), finding a lower pH, a negative correlation with luminosity, and the meat more tenderness with average value of 2.95 kgf /cm2 (P <0.05), associated with muscle stiffness or change in texture compared to industrial chicken meat, which may be indicative of pre-slaughter stress, an effect of physical activity of the semi-confined breeding, beyond genetic differences between muscle energy metabolism in chickens. Statistical differences were observed in relation to the protein of the thigh (15.7% and 18%), lipids for thigh (3.4% and 2.2%) and thigh (5.0% and 3.0%) for industrial and rustic free range chickens, respectively, possibly due to genetic and nutritional characteristics of the rearing system. Microbiological analysis showed satisfactory standard for fecal coliforms in all samples, according to Brazilian legislation, with average values of 2.45 log NMPg-1 for industrial and 2.75 log NMPg-1 for free-range chickens. Analysis of Salmonella spp. was more prevalent in free-range carcass (50%) compared to the industrial (25%), possibly due to handling and hygiene pre-slaughter. Thus, all the sensory attributes (odor, flavor, texture, juiciness and overall impression) were evaluated by the judges as slightly worse for freerange samples
Comparative characteristics of free-range and industrial chicken meat from west region of Rio Grande do Norte
Keywords: Ave de corte; Força de cisalhamento; Composição; Qualidade de carne; Análise sensorial; Broiler; Shear force; Composition; Meat qualiy; Sensorial analysis; CIENCIAS AGRARIAS::MEDICINA VETERINARIA